Pengembangan Media Pembelajaran Flipbook untuk Siswa Kelas IV Sekolah Dasar - Ilza Rahmatul Laily; Tri Linggo Wati (Indonesian Journal Publisher, 2026)
This study aims to develop and test the effectiveness of flipbook learning media on Indonesian cultural diversity material of fourth-grade elementary school students. The research used the Research and Development (R&D) method with the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Data collection techniques were carried out through validation by two media experts and two subject matter experts, as well as student and teacher response questionnaires. The result of the validation by media experts and subject matter experts each obtained a percentage of 100% with a category of Very Appropriate. The result of efectiveness test of the student response questionnaire obtained a percentage of 94,02% and the teacher response questionnaire obtained a percentage of 91,67% with a category of Very Appropriate. The flipbook media developed proved to be valid, practical, and effective as learning media.